Maqasid al-Syariah as a Framework for Religious Affairs Offices’ Role in Stunting Prevention - Haeruddin, Haeruddin; Miftahul Jannah; Muhrim Djakat; Kasim, Dulsukmi; Samsidar Jamaluddin (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2025)
Stunting remains a critical multidimensional crisis in Indonesia, with Cenrana District in Maros showing a significant increase in cases despite national reduction efforts. Although previous studies have examined the role of religious actors in health, few have analyzed their interventions through the philosophy of systemic law. This study investigates the strategic role of the Religious Affairs Office (KUA) in Cenrana in preventing stunting using Jasser Auda's Maqasid al-Syari'ah System Approach. Using a qualitative field research design, data were collected through interviews with KUA officials, health center staff, and village heads, supported by document analysis. This study reveals that KUA interventions operationalize three key system features in the maqasid system approach, namely Cognition, which reconstructs public understanding of stunting from “fatalistic destiny” to a threat to reason (Hifdz al-Aql); second, the features of Interrelated Wholeness and Hierarchy, which strictly enforce the age limit of 19 for marriage by integrating biological readiness into the validity of a legal marriage (Hifdz al-Nasl); and finally, the feature of Openness, which is demonstrated through cross-sector collaboration in which religious policies are validated by medical data. This study concludes that the KUA has shifted the Maqasid paradigm from mere protection (hifdz) to active human development (tanmiyah), positioning religious institutions as important agents in public health outcomes.